Tetraether biomarker records from a loess-paleosol sequence in the western Chinese Loess Plateau - Jia, Guodong; Rao, Zhiguo; Zhang, Jie; Li, Zhiyang; Chen, Fahu (Frontiers in Microbiology, 2013)
The ubiquitous occurrence of glycerol dialkyl glycerol tetraethers (GDGTs) in soils and their ability to record temperature and environmental changes offer the prospect of independently reconstructing continental paleotemperature and paleoenvironment from the loess-paleosol sequences (LPS) from the Chinese Loess Plateau (CLP). In this study we present records of GDGT-derived proxies for the last 70 kyr from the Yuanbao LPS, western CLP. Temperature record reconstructed from the cyclization and methylation index of branched tetraethers (MBT-CBT) displays that the onset of deglacial warming at ~20 kyr before present (BP) precedes the strengthening of summer monsoon at ~15 kyr BP, which is in agreement in timing with previous MBT-CBT temperature records from the southeastern CLP. The maximal deglacial warming of ~10 °C is slightly higher than those in the southeastern CLP, perhaps due to the higher latitude and farther inland of the study site. The Branched and Isoprenoid Tetraether (BIT) index shows higher values (0.87–0.96 range, 0.93 average) in the glacial loess and lower values (0.76–0.91 range, 0.83 average) in the Holocene paleosols, with a steady decreasing trend since the early Holocene. The decreasing trend could suggest enhanced Thaumarchaeota relative to GDGT producing bacteria activity since the early Holocene, but other possibilities, such as preferential degradation of isoprenoid GDGTs or upward increase in living archaea relative to bacteria in the paleosol profile, cannot be fully excluded. Our results thus demonstrate the need of future study on microbial community structure in soil column and differential degradation of GDGT molecules.